Constitutionalized Negligence - Deana Pollard Sacks (Washington University Law Review, 2012)
The propriety of imposing tort liability for negligent speech has been the subject of controversy since before the First Amendment’s incorporation. The debate over whether and to what extent civil liability may be socially desirable for unreasonably dangerous speech has intensified in recent years as entertainment media have become more explicitly violent and widely available. Experts have long concurred that exposure to all forms of violence is a cause of increased societal violence. Recent research on children’s brain development indicates that children are exceptionally vulnerable to violent media influences, and numerous risks to society are created by children’s exposure to violent video games in particular. Video games are a unique form of media due to their interactive and repetitive cognitive programming characteristics, which render them a special danger to children. Accordingly, the contemporary controversy over regulating allegedly unreasonably dangerous speech has centered on the harmful effects that violent video games can have on a child’s neurological and physiological health, which in turn can manifest in acts of violence toward others. Numerous state legislatures have responded to the scientific research by regulating the sale of violent video games to children. Lower federal courts have consistently declared such legislative action a First Amendment violation, and during the summer of 2011, the Supreme Court broadly declared that violent video games are fully protected speech and that state sales regulations are subject to strict scrutiny. The Supreme Court has never reviewed the constitutionality of imposing civil liability for unreasonably dangerous speech. Lower courts have generally rejected tort liability for speech on a theory of negligence. Further, lower courts have unanimously rejected tort liability for injuries allegedly caused by violent video games. The controversial scientific evidence concerning the harrowing potential effects that violent video games can have on children’s brains and behavior warrants review of the lower courts’ rules immunizing dangerous speech. A constitutionalized form of negligence liability for unreasonably dangerous speech that foreseeably causes actual injury should be considered, and the effects of violent video games on children present the most compelling case for recognizing such liability.